Genotype 3 is linked to worse liver disease progression in hepatitis C patients even after SVR following DAA therapy - Ran, Xiping; Xu, Yang; Wang, Ying; Zeng, Cheng; Gong, Chen; Wang, Ni; Cai, Dachuan (Frontiers in Cellular and Infection Microbiology, 2025)
Background and aimsHCV genotype (GT) 3 is associated with rapid liver disease progression. However, the liver disease progression and its risk factors in patients with HCV GT 3 infection after sustained virological response (SVR) following direct-acting antivirals (DAAs) remain unclear. Therefore, we aimed to investigate the liver disease progression of patients with GT 3 after SVR.MethodsThis was a retrospective cohort study of patients with HCV infection who achieved SVR by DAAs. The clinical outcome was overall liver disease progression (OLDP), defined as newly diagnosed compensated liver cirrhosis, decompensated liver cirrhosis, or hepatocellular carcinoma. The incidence of OLDP was evaluated by Kaplan−Meier analysis. Cox regression analysis identified the risk factors for OLDP.ResultsA total of 409 patients (46.9% GT3) were followed for 43.7 (32.9, 58.7) months. The incidence of OLDP was higher in patients with GT 3 (4.63/100PY) than non-GT 3 (0.60/100PY; P < 0.001). According to Cox multivariate analysis, GT 3 was significantly associated with OLDP (HR 6.41, 95% CI 1.82 - 22.56; P=0.004). The predictors of OLDP in patients with GT 3 were HCV recurrence (HR 12.15, 95% CI 3.18 - 46.46; P < 0.001) and FIB-4 > 3.25 (HR 16.40, 95% CI 1.03 - 39.81; P = 0.046) at baseline.ConclusionHCV GT 3-infected patients remain at a higher risk of OLDP even after achieving SVR by DAAs, especially patients with advanced liver fibrosis and at high risk for reinfection or virological late relapse.